PERAN PARTAI LOKAL DI ACEH BARAT DALAM MEWUJUDKAN POLITIK YANG DEMOKRATIS SESUAI DENGAN SISTEM KETATANEGARAAN INDONESIA (Studi Terhadap Dewan Pimpinan Wilayah Partai Aceh Aceh Barat) - Erick, Benni; Handoyo, Budi (Jurnal Sains Riset, 2022)
The Aceh local party is an organization formed by a group of Indonesians residing in Aceh on the basis of common desires and ideals to fight for the interests of each individual Acehnese people, the nation and the Indonesian state. In Indonesia's democratic and constitutional system, a local Aceh party is an activity or action carried out by an institution or organization that is regulated and carried out in accordance with applicable legal provisions. This research is an empirical study of how people think towards the law, looking at how they express their opinions and how they act in relation to the law. The results of the study found that local political parties in West Aceh played a role in creating a climate conducive to the unity and unity of the Indonesian nation, increasing people's political participation, and absorbing people's political aspirations. Local parties in Aceh have played a role in accordance with Indonesia's constitutional system. Despite the lack of political parties in the community, people have not been able to reap the benefits of the existence of local political parties because those who are elected as party representatives in the government do not carry out the role of the party as determined.Keywords: Local Parties, Democracy, Aceh, Politics